DBH -1021C>T and COMT Val108/158Met genotype are not associated with the P300 ERP in an auditory oddball task. - Spronk, D; Veth, C; Arns, M; Schofield, P; Dobson-Stone, C; Ramaekers, J; Franke, B; de Bruijn, E; Verkes, R (2013)
OBJECTIVE: The amplitude and latency of the P300 may be associated by variations in dopaminergic genes. The current study was conducted to determine whether functional variants of the catechol-O-methyltransferase (COMT) and dopamine beta-hydroxylase (DBH) gene were associated with P300 amplitude and latency in an auditory oddball task. METHODS: The P300 ERP was assessed by a two-tone auditory oddball paradigm in a large sample of 320 healthy volunteers. The Val108/158Met polymorphism (rs4680) of the COMT gene and the -1021C>T polymorphism (rs1611115) of the DBH gene were genotyped. P300 amplitude and latency were compared across genotype groups using analysis of variance. RESULTS: There were no differences in demographic characteristics in subjects for genotypic subgroups. No genotype associations were observed for the P300 amplitude and latency on frontal, central and parietal electrode positions. CONCLUSIONS: COMT Val108/158Met and DBH -1021C>T polymorphisms do not show evidence of association with characteristics of the P300 ERP in an auditory oddball paradigm in healthy volunteers. SIGNIFICANCE: We failed to find evidence for the association between dopaminergic enzymatic polymorphisms and the P300 ERP in healthy volunteers, in the largest study undertaken to date.